Supply Chain Added Value of Bell Pepper (Capsicum annuum L) in Candikuning Village, Tabanan, Bali - Cahyani, Ayu; Aviantara, I Gusti Ngurah Apriadi; Utama, I Made Supartha (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
The purpose of this study was to determine the added value of bell pepper value chains in Candikuning villageof Tabanan regency, Bali province. Sampling at the level of supply chain actors was carried out using the snowball sampling method. Meanwhile, sampling at the household consumer level was carried out using purposive sampling and non-probability sampling methods. Respondents in this study were farmers, collectors, Baturiti wholesale market traders, traditional market traders, city market traders, village vegetable traders and household consumers. In this study, the calculation of added value uses the Hayami and Kawagoe method. In selling bell pepper to collectors, the added value is Rp. 4,839.24 / kg, and a profit of Rp. 4,804.59 / kg. The sale of bell pepper to traders in the Baturiti Main Market resulted in an added value of Rp. 4,007.84/ Kg, and the profit obtained was Rp. 3,967.35 / Kg. The sales of bell pepper at the Baturiti Main Market traders obtained an added value of Rp. 3,138.99 / Kg, and the profits obtained were Rp. 3,117.17 / Kg. The sales of bell pepper by traditional markettrader added value of Rp. 4,325.97 / kg, and the profits obtained were Rp. 4,297.83 / kg. In selling paprika, the city market traders get an added value of Rp. 3,596.00 / kg with a value added value (ratio) of 7.55%. The profit obtained by market traders from the peppers being sold is Rp. 3,554.01 / Kg. The results of these researchindicate that farmers have the highest added value of Rp. 4,839.24 / Kg with a profit level of 13.72%, while Baturiti wholesale market traders have the lowest added value of Rp. 3,138.99 / Kg with a profit rate of 8.33. %.